No evidence of association between apo E polymorphism and BMI and lipids profile in Turkmen population - Ahani, Dr; S, Eshghinia; NM, Samaei; N, Mamizade (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Apolipoprotein E (apoE) is a glycoprotein that plays an essential role in lipid transport and metabolism.The present study purposed to determine the distribution of apoE alleles in a Turkman population and its association with lipid profile. In a cross-sectional study 354 healthy Turkman were recruited. Fasting blood samples were collected for biochemical tests and DNA extracting. Genomic DNA was amplified using PCR-RFLP method. The resulting fragments of PCR product digestion were detected by polyacrylamide gel electrophoresis. This study showed that Îµ3 allele and E3/E3 genotype are the most common allele and genotype, while Îµ2 and Îµ4 alleles had lower frequencies, respectively. Two homozygote genotypes E2E2 and E4E4 were not detected in our sample. Results didn’t confirm any association between apo E polymorphism with lipids concentration in Turkmen population.